Balancing Sharia and Spirituality: Gus Baha’s Interpretation of Wahdatul Wujud in the Teachings of Siti Jenar - Sidiq, Muhamad Yusuf (DINIKA : Academic Journal of Islamic Studies, 2025)
This study analyzes perspective of K.H. Ahmad Baha’udin Nursalim, known as Gus Baha’, on the Wahdatul Wujud teachings of Siti Jenar, focusing on the limitation of its dissemination to the general public. Gus Baha emphasizes that while the teachings are not fundamentally erroneous, they are highly susceptible to misinterpretation, potentially leading to religious deviations such as neglecting Sharia and fostering absolute truth claims that cause social division. Aligning with the Walisongo’s stance, he argues that advanced Sufi teachings should be studied only by intellectuals or those with sufficient spiritual capacity to prevent confusion. Using a qualitative descriptive method and literature review, the study collects data from Gus Baha’s sermons, writings, and historical analyses of Walisongo and Siti Jenar. The analysis explores the Wahdatul Wujud concept within Sufi thought and its relevance in Indonesian Islam. Findings reveal that Gus Baha’s moderate approach seeks to balance Sharia and spiritual essence, ensuring Sufism remains beneficial without compromising faith. Therefore, a correct understanding of Wahdatul Wujud can serve as a spiritual foundation for a harmonious and devout society without neglecting Islamic law.